The Fama-French Five-Factor Model: Evidence of the Emerging Markets Exchange Traded Funds Performance - Korenak, Boris (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
The main purpose of this study is to provide an insight into the investment performance of emerging markets’ exchange-traded funds. The Fama-French five-factor model was used to perform the regression of the returns of individual exchange-traded funds that have exposure to emerging markets, against the model’s factors. The study uses monthly returns and covers the period from August 2017 until December 2021, due to the exchange-traded funds’ inception date the track record was limited. Overall, the findings are in the line with the Fama-French five-factor model initial results. According to these results, expected positive contributors to the investment performance are, in the presented order of importance, market premium and small-capitalization, as well as funds’ tilt towards stocks of the companies with strong operating profit and conservative investing policy. However, there is one exception and that is the growth style that outperformed the value style. Therefore, the value-style tilt of some of the emerging markets’ exchange-traded funds led to negative performance contributions, because the style was out of favor. At the same time, during the observed period, there were no exchange-traded funds that delivered statistically significant alpha. Moreover, only one of emerging markets’ exchange-traded fund produced a positive alpha, the other three underperformed in relation to the adequate benchmark as per the Fama-French five-factor model.